Transcriptome analyses identify 10 deregulated hub genes and essential molecular mechanisms in early-onset colorectal cancer - Nguyen, Hieu Duc; Chen, Ming-Jenn; Lee, Chung-Ying; Ni, Yi-Chun; Yee, Ke Xin; Wu, Yung-Fu; Lee, Kuen-Haur (Frontiers in Oncology, 2025)
IntroductionThe rapid increase in early-onset colorectal cancer (EoCRC) case numbers in recent years indicated an urgent need to identify the essential mechanisms and markers for EoCRC diagnosis and treatment. Therefore, this study aimed to analyze the metadata to overcome the limitation of the sample number of previous EoCRC research and to identify central mechanisms and genes that are crucial for EoCRC.MethodsThis study employed statistical analysis of data from the cBioPortal and GEPIA databases to identify overexpressed EoCRC genes. Using a protein–protein interaction map, it identified hub genes. The function of these genes was clarified via risk model, survival, and cell model analysis.Results and DiscussionThe results of clinical data analysis showed an increased rate of late-stage diagnosis and a lower overall survival of the EoCRC cohort. A total of 953 enriched gene samples were detected in EoCRC and 89 genes were identified as EoCRC overexpression genes. From the protein–protein interactions among 53 genes, the top 10 hub genes showed potential for EoCRC diagnosis and prognosis by linking gene expression to diagnosis and survival analysis data. The knockdown of four selected hub genes in the cell model identified the association of EoCRC overexpression hub genes with tumor development and suggested their role in mTOR signaling, cell cycle, and apoptosis regulation. In summary, the study analyzed molecular and clinical data to identify hub genes associated with cancer prognosis in patients with EoCRC. These genes may serve as targets for diagnosis and treatment.